Experimental study of buoyancy-induced instability in the DME and LPG jet diffusion flame. (1st May 2021) - Mahesh Nayak, G.; Kolhe, Pankaj; Balusamy, Saravanan
Graphical abstract: Highlights: The buoyant DME and LPG jet diffusion flames are studied for Re = 250–2000. Fuel jet interacts with outer vortices at subharmonic frequencies. The vortex merging leads to alternating flame bulge upstream of the tube exit. DMD captures the spatial characteristics of the flame vortex dynamics. Abstract: An experimental study is conducted on the buoyant jet diffusion flames to explore the interaction between the fuel jet and the outer vortex and their impact on the flame structure. Dimethyl ether (DME) and liquefied petroleum gas (LPG) diffusion flames are investigated. A laminar diffusion burner setup is used to study the flame dynamics of three different tube diameters (6, 8, and 10 mm) over a wide range of Reynolds numbers (250–2000). Flame flicker frequencies are analyzed using chemiluminescence signals and image processing techniques, and high-speed Schlieren images visualized flame dynamics and structure. The spatiotemporal structure of jet diffusion flames is analyzed using the dynamic mode decomposition (DMD) tool. Analysis of the Schlieren images revealed that the outer vortex structure interacts with the fuel jet, which eventually leads to convective feeding to the outer vortical structure. The outcome is the radial expansion of the leading vortex, which allows the trailing vortex to merge and produce a subharmonic frequency. However, all test conditions, regardless of the presence of subharmonic frequency in the buoyant diffusion flame, follow the established relationship between Strouhal-Froude numbers. The dominant mode of DMD captured the spatial features of the outer vortex at associated temporal frequencies. The large-scale coherent structure is observed in the region of subharmonic oscillation due to the merging of successive vortices. This process occurs at the alternate flame bulge formed near the tube exit.